Understanding Grammars through Diachronic Change - Madariaga, Nerea (Frontiers in Psychology, 2017)
In this paper, I will vindicate the importance of syntactic change for the study of synchronic stages of natural languages, according to the following outline. First, I will analyze the relationship between the diachrony and synchrony of grammars, introducing some basic concepts: the notions of I-language / E-language, the role of Chomsky’s (2005) three factors in language change, and some assumptions about language acquisition. I will briefly describe the different approaches to syntactic change adopted in generative accounts, as well as their assumptions and implications (Biberauer et al 2010, van Gelderen 2004, Lightfoot 1999, 2006, Roberts 2012). Finally, I will illustrate the convenience of introducing the diachronic dimension into the study of at least certain synchronic phenomena with the help of a practical example: variation in object case marking of several verbs in Modern Russian, namely, the verbs denoting avoidance and the verbs slušat’sja ‘obey’ and dožidat’sja ‘expect’, which show two object case-marking patterns, genitive case in standard varieties and accusative case in colloquial varieties. To do so, I will review previous descriptive and / or functionalist accounts on this or equivalent phenomena (Jakobson 1936 [1984], Clancy 2006, Nesset and Kuznetsova 2015a,b). Then, I will present a formal –but just synchronic- account, applying Sigurðsson’s (2012) hypothesis on the expression of morphological case to this phenomenon. Finally, I will show that a formal account including the diachronic dimension is superior (i.e. more explanative) than purely synchronic accounts.